Teaching Visual Arts to Preschool Children - Mamajonova Khushroy Shavkatovna (International Journal on Orange Technologies, 2021)
This article emphasizes that the preparation of preschool children for visual activities from an early age serves to direct their interests and aspirations in the right direction